2020
DOI: 10.1186/s40543-020-00232-8
|View full text |Cite
|
Sign up to set email alerts
|

Method development for acetyl octapeptide-3 analysis by liquid chromatography-tandem mass spectrometry

Abstract: Background: Acetyl octapeptide-3 (SNAP-8) is an antiaging peptide that is more effective than acetyl hexapeptide-3, which is more stable than botulinum toxin and effectively relieves facial wrinkles. Products containing SNAP-8 such as patch are producing, but analytical method has not been reported to determination of SNAP-8. Method: Mobile phase, collision energy, and desolvation line temperature were optimized, and mass spectral data set for SNAP-8 was newly constructed by liquid chromatography-triple quadru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In addition, analysis of a commercial formulation of botulinum toxin showed that the drug elutes without interfering peaks generated by excipients in the commercial product. [6][7][8][9][10][11] Therefore, we found the method results to be stable for different parameters.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, analysis of a commercial formulation of botulinum toxin showed that the drug elutes without interfering peaks generated by excipients in the commercial product. [6][7][8][9][10][11] Therefore, we found the method results to be stable for different parameters.…”
Section: Discussionmentioning
confidence: 99%
“…An example of Argireline derivative is acetyl octapeptide-3 with the sequence: Ac-Glu-Glu-Met-Gln-Arg-Arg-Ala-Asp-NH 2 . This peptide is more effective in wrinkle improvement than Argireline [29].…”
Section: Argireline Analogs -Structure--activity Relationshipsmentioning
confidence: 90%
“…3, structure B) determination in biodegradable microneedle patches. The sample preparation consisted of extraction with water and filtration, due to the relatively simple matrix of microneedle load [29].…”
Section: The Content Of Argireline In Cosmetic Productsmentioning
confidence: 99%
See 1 more Smart Citation